Diffusion Smart-seq3 of breast cancer spheroids to explore spatial tumor biology and test evolutionary principles of tumor heterogeneity - Antony Cougnoux; Loay Mahmoud; Per A. Johnsson; Alper Eroglu; Louise Gsell; Jakob Rosenbauer; Rickard Sandberg; Jean Hausser (Scientific Reports)
Abstract Combining 3D cultures such as tumor spheroids and organoids with spatial omics holds great potential for tissue biology and cancer research. Yet, this potential is presently limited by technical and financial challenges of spatial omics methods and 3D cultures. To address this, we combine dye diffusion, the Smart-seq3xpress protocol for deep single-cell gene expression profiling, and dedicated probabilistic inference methods into diffusion Smart-seq3 (Smart-seq3D), to reveal the transcriptome of single cells along with their position along the core-periphery axis of spheroids. Applying Smart-seq3D to triple-negative breast tumor spheroids identifies thousands of spatial genes and reveals continuous, ungated spatial gene expression. Spatial gene and pathway expression patterns suggest biologies specific to spheroid regions, which we validate by immunostainings and pharmacological interventions. We use the Smart-seq3D data to test evolutionary principles of spatial tumor heterogeneity. Finally, we characterize aspects of tumor heterogeneity captured by 3D spheroids that are missing from 2D cultures but found in tumors in vivo. Smart-seq3D can offer a cost-efficient approach to explore how cells adapt their transcriptome to different micro-environments, reveal spatial determinants of drug resistance and could serve to characterize spatial interactions between cancer and stromal/immune cells in 3D co-cultures.